Pengaruh Level Pupuk Organik Cair Top G2 terhadap Kandungan Protein Kasar, Serat Kasar dan Lemak Kasar Rumput Gajah Mini (Pennisetum Purpureum Cv. Mott) Panen Kedua - Leta, Lidia Eka; Temu, Stefanus Tany; Osa, Dominggus B.; Nastiti, H. P. (Yayasan Sumber Daya Manusia Cerdas, 2025)
This study aimed to analyze the effect of different doses of TOP G2 liquid organic fertilizer on the crude protein (CP), crude fiber (CF), and crude fat (CFat) content of mini elephant grass (Pennisetum purpureum cv. Mott) during the second harvest. A completely randomized design (CRD) with four treatments and four replications (16 experimental units) was applied. The treatments included: M0 (control, no fertilizer), M1 (10 mL TOP G2/L water), M2 (20 mL TOP G2/L water), and M3 (30 mL TOP G2/L water). Proximate analysis (Kjeldahl, Weende, and Soxhlet methods) was used to measure CP, CF, and CFat levels. ANOVA results indicated no significant differences (P>0.05) in CP, CF, or CFat content across treatments. The average values were 12.49% CP, 29.68% CF, and 1.68% CFat. These results suggest that TOP G2 application, up to 30 mL/L, did not significantly alter the nutritional quality of mini elephant grass in the second harvest. Further studies are recommended to explore higher doses or combined fertilization strategies.